Rooting of Chir Pine (Pinus roxburghii Sakg.) Cuttings under Mist by Using Powder Mixtures - Bora, P.; Khosla, P. K. (Indian Forester, 1994)
Cuttings prepared from the terminal portion of the shoots of current year growth of 12 year old Chir pine (Pinus roxburghii Sarg.) plants rooted under mist. Four rooting powder mixtures of 0, 0.5, 1.0 and 1.5 per cent IBA with 10 per cent each of sucrose and captan in talc were tested. As high as 31.25 per cent mean rooting and better root quality were observed in mixture containing 1 per cent IBA and 10 per cent each of sucrose and captan.